Creating multilingual spaces through arts-based methods in foundation phase classrooms - Aung, Shine (Frontiers in Education, 2025)
This article considers how the use of multiple languages and the incorporation of arts-based methods in the Foundation Phase (Grades 1 to 3) classroom led to the creation of a third space, which is characterised by openness and creativity. A third space is transformative in nature, as it facilitates the process of cultural exchange among traditions that creates new identities, values, and practices. By facilitating ‘new’ learning, parents, teachers, and learners share their cultural artefacts, co-construct knowledge, and connect home and school literacies. The study took on an interventionist approach which incorporated the theories of third space, arts-based enquiry and multimodality to create a space that incorporated innovative pedagogies. The findings indicate that by allowing learners to create meaning through multilingualism, multimodalities and arts-based methods improved their language skills. Participating learners’ understanding of reading passages improved when they were allowed to express their cognition through a combination of drawings, multilingual discussions and writing, as opposed to answering in writing only. In the South African context, many people are able to speak more than two languages. Therefore, both multilingualism and arts-based methods can be used to create innovative pedagogical practices in the classroom to enhance literacy development.